Uso de videojuegos y conducta agresiva en adolescentes de la Unidad Educativa Adolfo Valarezo, periodo 2022-2023 - Ríos Quezada, Marco Joel (2023)
The problematic use of video games and aggressive behavior in adolescents has become a global concern of great impact and interest, because it affects the normal development of the individual in various areas of development such as social, individual, family and academic relationships, among others; thus affecting the mental health of this population. The main objective of this research is to determine the relationship between the use of video games and aggressive behavior in adolescents of the Adolfo Valarezo Educational Unit. The study had a non-experimental, cross-sectional, exploratory, descriptive and correlational design. The sample consisted of 104 participants, which were established by non-probabilistic sampling and selection criteria. The instruments used for data collection were the Questionnaire of Experiences Related to Video Games and the Buss and Perry Aggressiveness Questionnaire. The results indicate the presence of problematic use of video games in most adolescents and the presence of hostility-type aggressiveness, which represents a low level of aggressive behavior in adolescents. In conclusion, a statistically negative relationship is determined between both study variables, because, as the problematic use of video games increases, the level of aggressive behavior remains at a low level, this being the level of hostility, however, it is important to mention that for aggressive behavior to develop, other factors must be involved. To conclude, a psychotherapeutic intervention plan for problematic video game use and aggressive behavior was designed, which aims to modify maladaptive behaviors and thoughts in adolescents through the cognitive behavioral model